Vulnerbility Of Gpon Network Elements - Chlapek, Jan (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2019)
Passive optical network (PON) is a promising access network technology used in modern telecommunications. Due to their passive nature PONs are potentially vulnerable against a number of security threats. This paper is focused on testing the resilience of a GPON (Gigabit PON) network against a DoS (Denial of Service) attack, conducted with a CW (Continuous Wave) laser plugged into the optical splitter. The goal was to cause signal interference on the feeder fiber to prevent communication between the OLT (Optical Line Termination) and ONUs (Optical Network Unit).
Keywords: DoS; Security; GPON; PON; Passive Optical Network